Mapping the Humification Degree for Sustainable Development of Peat - Laura, Dines Ngau (UNIMAS Institutional Repository, 2023)
Tropical peatlands in the Southeast Asia are commonly deforested, burned, and drained due to the increase of economic and social pressures for peatlands to be converted into agricultural sites for economic development. The state of Sarawak, Malaysia has the largest peat area of approximately 1.6 Mha in which an extensive proportion of it has been developed into agricultural plantations such as oil palm estates. However, the cultivation of these crops on peatlands in Malaysia has been a divisive subject; previous studies hypothesized that peat humification degree is a significant factor in controlling palm growth (i.e., lower yield is observed when the crops are planted on less humified peat), whereas other reports highlighted the importance of good water table management as one of the main factors in ensuring positive plant growth. Additionally, the conversion of tropical peat forest into agricultural plantation has also caused the latter to undergo extreme changes affecting soil moisture dynamics, vegetation composition, organic matter decomposition process, nutrient availability, and carbon fluxes. Considering the environmental impacts of peatland alteration due to anthropogenic disturbances, it is crucial that existing cultivated peatlands be managed, developed, and utilized in a more sustainable manner. Therefore, this study was set out to investigate peat characteristics (soil moisture, elemental content, pH, EC, momentary total CO2 emission), as well as to map out peat soil moisture and humification degree using atomic C/N ratio, in cultivated peat under oil palm plantation in contrast to that of an uncultivated secondary forest peat. Peat soil samples were collected from one-hectare plots of 25 20 m × 20 m subplots in Sebungan Oil Palm Plantation and Sabaju Secondary Forest at two depths: 0 – 50 cm and 50 – 100 cm. These samples were dried in the oven at 55 ℃ and sieved into fine particles. Samples were then subjected to elemental analysis, FTIR, pH and EC analyses. Momentary total CO2 emission was also measured during sampling. Peat soil moisture and C/N ratio data were spatially interpolated using the QGIS software. The oil palm plantation clearly showed lower moisture content at both peat profiles (0 – 50 cm and 50 – 100 cm) compared to the secondary forest. The growth of oil palm trunks showed a significant positive correlation with the topsoil moisture; observed through the soil moisture map, oil palms showing negative growth in trunk diameter were in relatively drier subplots or near to the drain. C/N ratio in the secondary forest was substantially lower (i.e., lower C/N ratio indicates more humified peat) than the oil palm plantation as the former was characterized with higher N content. Contrastingly, the humification index calculated based on the functional group characteristics in FTIR indicated that the plantation peat was enriched with carboxyl and carbonyl groups suggesting that plantation peat was at the more advanced stage of humification. These results give an indication that C/N ratio as a humification degree indicator of the two ecosystems cannot be compared directly due to their differences in N-cycling ecology. In the oil palm plantation, the topsoil C/N ratio map highlighted that oil palms which grow on peat with lower C/N ratio (more humified) produced more fronds with greater diameter size, whereas palms producing lower number of fronds were in areas with relatively higher C/N ratio (less humified). pH value in the topsoil profiles in both plantation and forest were significantly lower than at 50 – 100 cm while EC was observably higher in the oil palm plantation as a result of decreased organic matter input. Lastly, the momentary total CO2 emissions in the secondary forest was observed to be significantly higher than the oil palm plantation. Overall, this study confirms that changes in land use, especially drainage and vegetation removal, modify the soil-water dynamic and rate of humification in tropical peatlands. The use of maps in this study has also provided better insights into the spatial heterogeneity of peat characteristics at a local scale and could be useful for a more effective management of tropical peatlands in the future.